The Modified Caldwell-Luc Approach with the Use of Collagen Material for Treatment of a Chronic Perforated Maxillary Sinusitis - Ekaterina Diachkova; Elena Morozova; Natalia Blagushina; Svetlana Tarasenko (Hindawi Limited, 2020)
Oroantral fistula (OAF) often develops after extraction of posterior maxillary teeth and requires surgical closure. If it persists, OAF may result in maxillary sinusitis. This paper reports a case of an oroantral fistula, associated with chronic maxillary sinusitis. A 46-year-old female patient presented with a history of traumatic tooth extraction, which led to OAF formation. Three unsuccessful attempts were made to close it elsewhere. With one operation, we performed Caldwell-Luc surgery and closed OAF with a collagen membrane and plug and a buccal flap. The patient was assessed at 1-, 3-, 6-, and 12-month and 8-year follow-up visits, with no signs of maxillary sinusitis or OAF recurrence being found with the efficient amount of bone and opportunity for further dental rehabilitation like sinus lifting and dental implantation. We believe that this approach may be a viable option in similar cases.